KONSTRUKSI HAJI MISBACH SEBAGAI ANCAMAN DALAM PERS KOLONIAL HINDIA BELANDA (1924) - Bella Riskika Taufik; Iin Isnaini (Universitas Muhammadiyah Bandung, 2026)
A This article aims to analyze how Haji Mohammad Misbach was represented as a threatening figure in colonial discourse through coverage in the newspaper Algemeen Handelsblad voor Nederlandsch-Indië in 1924. This study departs from the limitations of previous research that tended to place Misbach within a historical, political, and ideological framework, without specifically examining the process of constructing his image in colonial media. This research utilizes historical methods combined with a discourse analysis approach, using the text